Strain sensing in composites using aligned carbon nanotube sheets embedded in the interlaminar region. (November 2016) - Aly, Karim; Li, Ang; Bradford, Philip D.
Abstract: This paper introduces a novel technique for embedding aligned sheets of two millimeters long, interconnected CNTs into the interlaminar region of composite structures. The potential of these embedded CNT sheets to function as damage detecting and strain sensing elements was demonstrated via various mechanical tests that were accompanied by real time electrical resistance change data acquisition. The experimental results suggested that the CNT sheet sensitivity could be further enhanced by an oxygen plasma treatment and also by pre-straining the CNT sheets before embedding them. The samples containing two CNT sheets layers exhibited long term stability, sensitivity and repeatability which are vital features for health monitoring.